Development and analysis of advanced precast dry connections for concrete-encased concrete-filled steel tube columns - Zhu, Gaoming (Nanyang Technological University, 2024)
Despite superior structural performance, CECFST members so far have not been widely used in developed countries with severe manpower crunch due to a lack of workable precast connections. Provided that the CECFST members are utilized to replace conventional RC or CFST members, considerable cost saving could be achieved due to inherent advantages of CECFST members. In this regard, this study was initiated at Nanyang Technological University, Singapore (NTU) to promote the application of CECFST members. This research programme includes development of connection detailing and investigation of connection mechanical performance. Taking multiple key factors to the success of precast construction into consideration, such as fabrication cost, construction sequence, aesthetics, construction tolerance, transportation as well as speed of assembly and manpower, two types of precast connections were proposed. Compared with conventional CIP connections, the proposed precast connections featured reduced manpower demand on-site and rapid assembly on-site. Compared with existing connections, configuration of the proposed precast connections was rather advanced, to ensure structural safety, laboratory tests are required to examine the connection effectiveness. Thus, to study structural behaviour of the proposed connections, a level-by-level experimental programme was initiated, from connection to column and then towards sub-structure level. The overall experimental programme included four test series, which consisted of eleven connection tests, six column tests and seven sub-structure tests. Key parameters such as connection detailing, load eccentricity, column slenderness ratio, and connection location along the column height were studied in the experimental programme. In addition to the systematic experimental programme concluded above, elaborate 3D finite element models were developed to simulate the proposed precast connection. To ensure fidelity of numerical simulations, 3D solid FE models were established through ABAQUS software package 6.14. The FE models were verified against the test results, including load versus displacement relationship and failure mode. With the verified FE models, extensive parametric studies were conducted for the second and third test series, which provided substantial research data for a deeper discussion on connection and column performance. Based on the obtained experimental and numerical results, simplified analytical models have been proposed to predict tension and compression resistance of the proposed precast connection. A simplified mechanical model was developed to determine ductility of the precast connection, followed by a simplified tensile strength prediction model. These two models were verified against the test results. Moreover, as per the plastic stress distribution (PSD) method suggested by EN 1994-1-1, a simplified mechanical model was proposed to calculate compression resistance of the proposed connection, namely the N-M interaction curve. This provides structural engineers with a straightforward connection strength calculation approach without undertaking further laboratory tests or time-consuming numerical modelling.